Gorlin Syndrome Presentation and the Importance of Differential Diagnosis of Skin Cancer: A Case Report - Ravina Sangera-Grewal; Parbeer Singh Grewal (Frontiers Media S.A., 2018)
In a busy community practice, clinical skin findings can often be misinterpreted. Skin cancers can sometimes mimic rashes like psoriasis, eczema or prurigo nodularis in both appearance and symptoms. Gorlin syndrome is one such genetic syndrome, characterized by the eruption of multiple and early onset basal cell carcinomas (BCCs), which can be mistaken for a rash. We describe a 68-year-old female who presented to the dermatology office with a previous history of over 30 BCCs that had been previously biopsied and/or surgically removed. However, the patient had been lost to follow up for several years and had not been seen by a skin specialist. In the interim, she had been misdiagnosed as having eczematous or psoriatic lesions by primary care providers. Patients with Gorlin syndrome are even harder to diagnose as their skin cancers often do not possess the classic features associated with a basal cell or squamous cell carcinoma. When in doubt, and especially if failing topical therapy, patients presenting with dermatological lesions should be properly referred to a specialist for further assessment and workup.